2015
DOI: 10.1148/radiol.2015141728
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion Diffusion-weighted Imaging of Multiple Myeloma Lesions: Correlation with Whole-Body Dynamic Contrast Agent–enhanced MR Imaging

Abstract: Diffuse bone marrow involvement is associated with increased D. Hypervascular focal lesions with high maximal enhancement value of focal lesions also show high f value. Likewise, the decreased maximal enhancement value of focal lesions after treatment is accompanied by decreased f.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 49 publications
2
36
1
Order By: Relevance
“…Studies have indicated that the high f value of the head and neck malignant tumor suggests poor prognosis . Bourillon and other studies on multiple myeloma showed that f value of bone marrow lesions was positively correlated with the maximum enhancement degree of the tumor. Compared with the CR group, high cellularity of the bone marrow and more blood supply could cause higher bone marrow blood flow in NR group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the high f value of the head and neck malignant tumor suggests poor prognosis . Bourillon and other studies on multiple myeloma showed that f value of bone marrow lesions was positively correlated with the maximum enhancement degree of the tumor. Compared with the CR group, high cellularity of the bone marrow and more blood supply could cause higher bone marrow blood flow in NR group.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement was interpreted according to the interclass correlation coefficient as: 0, poor; 0.01-0.20, minor; 0.21-0.40, fair; 0.41-0.60, moderate; 0.61-0.80, major; and 0.81-1.00, almost perfect. 17 We used the Mann-Whitney test to compare sizes of the areas of the ROIs, ADC values, kurtosis, and skewness between uterine carcinosarcomas and endometrial carcinomas, with P < 0.05 considered statistically significant. We performed receiver operator characteristic (ROC) curve analyses based on positive test results for patients with carcinosarcomas to identify the optimal cutoff for maximizing the sum of sensitivity and specificity, and we examined the area under the ROC curve (AUC) to assess the diagnostic abilities of ADC values, kurtosis, and skewness.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were correlated with those provided by the first observer, and concordance of interobserver variability was tested by calculating Spearman and interclass correlation coefficients. Agreement was interpreted according to the interclass correlation coefficient as: 0, poor; 0.01–0.20, minor; 0.21–0.40, fair; 0.41–0.60, moderate; 0.61–0.80, major; and 0.81–1.00, almost perfect …”
Section: Methodsmentioning
confidence: 99%
“…As a result, the IVIM technique can now be applied to various tissues. Surprisingly, however, only a very limited number of IVIM studies have been performed on bone marrow . This might be due to lipids, which represent a major confounding factor in the quantification of both diffusion and perfusion .…”
mentioning
confidence: 99%